2017
DOI: 10.1016/j.socscimed.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Childhood deprivation and later-life cognitive function in a population-based study of older rural South Africans

Abstract: Rationale Little research has evaluated the life course drivers of cognitive aging in South Africa. Objectives We investigated the relationships of self-rated childhood health and father’s occupation during childhood with later-life cognitive function score and whether educational attainment mediated these relationships among older South Africans living in a former region of Apartheid-era racial segregation. Methods Data were from baseline assessments of “Health and Aging in Africa: A Longitudinal Study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
68
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 51 publications
10
68
0
Order By: Relevance
“…A growing number of studies regarding late-life cognition have concentrated on the effects of early-life and late-life factors, such as childhood deprivation and adversity, adult socioeconomic status (SES), and lifestyles. [9][10][11][12] Childhood SES is a powerful predictor of health outcomes in later life, always measured by the parental education and occupation or household income. Recently, emerging data have indicated that both higher childhood and adult SES can prevent poor cognitive function in later-life.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies regarding late-life cognition have concentrated on the effects of early-life and late-life factors, such as childhood deprivation and adversity, adult socioeconomic status (SES), and lifestyles. [9][10][11][12] Childhood SES is a powerful predictor of health outcomes in later life, always measured by the parental education and occupation or household income. Recently, emerging data have indicated that both higher childhood and adult SES can prevent poor cognitive function in later-life.…”
Section: Introductionmentioning
confidence: 99%
“…The major limitations in these studies is the difficulty of ruling out the confounding influence of individual characteristics such as intelligence or childhood socioeconomic status that may influence both schooling and late-life cognition. Evidence from studies in settings with very different confounders [5], or based on natural experiments that could not plausibly be influenced by individual characteristics [6], strengthens the overall evidence base, even if the new studies have different limitations.…”
mentioning
confidence: 78%
“…Survey data were collected by trained local fieldworkers using a Computer Assisted Personal Interviews platform in the local xiTsonga language. We assessed three exposures: Cognitive function: a continuous z‐standardized latent variable (mean 0, standard deviation (SD) 1) representing time orientation (ability to state the correct day, month, year and South African president), immediate and delayed recall of 10 words read out loud by the interviewer, and numeracy (ability to count from 1 to 20 and to finish a number skip pattern) . The cognitive function z‐score was derived using confirmatory factor analysis (CFA) with a robust weighted least squares estimator, which used the common covariation between the individual cognitive test items to generate a latent cognitive function z‐score.…”
Section: Methodsmentioning
confidence: 99%